Design of Lightning Strike Hazard Zone Detection System for Direct Lightning Strike Prevention in Open Area - Nugraha, Adi; Al Bantani, Rahmat Ato'ullah Gumilang; Grahito; Yudono, Muchtar Ali Setyo; Suryana, Anang (Universitas Nusa Putra, 2024)
Lightning is a dangerous natural phenomenon due to its high-voltage electrical energy, which can cause significant damage. The primary hazard of lightning is direct strikes, potentially leading to severe burns, organ failure, and even death. Additionally, lightning can trigger fires, disrupt power grids, and cause explosions. To mitigate these risks, this research focuses on designing a lightning detection system using the